Safety and efficacy of misoprostol versus manual vacuum aspiration in missed abortion up to 12 weeks - Swati, Badgire; Sonali, Deshpande; Shrinivas, Gadappa; Mohini, Patil (Nepal Journal of Obstetrics and Gynaecology, 2020)
Aims: To compare the safety and efficacy of Misoprostol versus manual vacuum aspiration in missed abortion up to 12 weeks. Methods: This is comparative study where Misoprostol 800 μg was administered sublingually four hourly till expulsion of products or maximum of three doses in one group and 400 μg misoprostol followed by manual vacuum aspiration 4 hours later was done under local anaesthesia in another group from October 2019 to March 2020 at Government Medical College and Hospital, Aurangabad, Maharashtra. Unpaired t-test and Chi squared test were performed with alpha-error set at 0.05. Results: The success rate in Misoprostol group was 88 % and in the MVA group, it was 98%. Mean duration of hospital stay in Misoprostol group was 2.46±1.18 days and in MVA group was 1.55 ± 1.52 days (p= 0.3). Mean induction abortion interval in Misoprostol group was 8.125±3.29 and 4.46±0.44 hours in MVA group (p=0.000). One woman from MVA group had perforation of uterus which could be attributed to previous LSCS with tight os. Conclusion: Single dose of Misoprostol followed by manual vacuum aspiration is better than the multiple dosage of Misoprostol for the treatment of first trimester missed abortion in terms of duration of treatment but not for the individual success rate. Hospital stay is similar. Keywords: manual vaccum aspiration, misoprostol, missed abortion